The effect of polishing technique and curing time on surface properties of a bulk-fill resin composite - Dupont, Airald; Lahtinen, Karri (My University, 2020)
Aim. The purpose of this in vitro study was to determine the effects of different polishing protocols and curing times on the surface roughness (SR), surface gloss (SG) and surface hardness (SH) of a bulk-fill resin composite (BRC). Material and methods. A total of 30 block-shaped specimens (40 mm length × 10 mm width × 2 mm thick) were made from Filtek bulk-fill resin composite (3M ESPE, USA) and divided into two groups (n=15) according to curing time (10 and 40 seconds). Each group was subdivided into five groups (n=3), according to polishing protocol: Laboratory polishing with different silicon paper grits (G1: 1200) → (G2: 2400) → (G3: 4000). Chairside polishing using a series of Sof-Lex spiral (G4) and Jiffy Polisher points (G5). SR was measured by surface profilometer. A vickers indenter was used for testing SH and Glossmeter was used to determine the SG at 60°. SR, SG, SH were quantified before and after polishing. Scanning electron microscopy (SEM) evaluation was then performed. Results. ANOVA revealed that curing time had no significant effect (p>0.05) on tested surface properties of BRC. Significant differences in SR (ranged 0.1-2 μm) and SG (ranged 20-90 GU) were found according to the type of polishing protocol (p<0.05). SH values following different polishing protocols were significantly higher (ranged 82-95 VH) than polishing values obtained before polishing protocols (p<0.05). Conclusion. The tested chairside polishing protocols presented lower SG and higher SR values than laboratory polishing protocols.
Keywords: bulk-fill resin composite, surface properties, polishing protocol, curing time